J.Co Donuts & Coffee’s Consumer Satisfaction - Intan Permana (Entrepreneurship Faculty, Universitas Garut, 2020)
This research dicusses customer satisfaction. Researcher will use desriptive design in advance to get insight and understanding about research problem, and then the result from descriptive design will be used as input for conclusive research is 66 respondents. The result of this research shows that customers will be satisfacted to consumption J.Co Donuts, J.Pops Baby Donuts, J.Coffee, J.Cool and J.Club if J.Co Donuts & Coffee offered the good innovation attributes, change behavior, suitability of offering and quality of service.